Deformation‐resistant Ta0.2Hf0.8C solid‐solution ceramic with superior flexural strength at 2000°C. Issue 1 (27th August 2021) - Demirskyi, Dmytro; Borodianska, Hanna; Nishimura, Toshiyuki; Suzuki, Tohru S.; Yoshimi, Kyosuke; Vasylkiv, Oleg
Abstract: In this study, we explored the consolidation, solid‐solution formation and high‐temperature properties of tantalum hafnium carbide with the 1 TaC:4 HfC ratio, that is, Ta0.2 Hf0.8 C. Tantalum hafnium carbide bulks can be consolidated using spark‐plasma sintering only at temperatures exceeding 2200°C. The bulks prepared using a 40‐min dwell at 2200°C had the lattice parameter a = 4.571(9) Å. Based on the three‐point flexural tests, it was observed that the toughness and strength of Ta0.2 Hf0.8 C remained high at 2000°C (3.4 ± 0.4 MPa m 1/2, 500 ± 20 MPa). At 2000°C, majority of carbides show a plastic behavior, but the strain‐stress curves of the SPSed Ta0.2 Hf0.8 C ceramic were linear. Using the shrinkage rate data during the SPS and the strain‐stress data from the high‐temperature flexure, we estimated the activation energies for the densification and flexure as 820 ± 20 kJ/mol and 1180 ± 120 kJ/mol, respectively.